eSaku: An Interactive Mobile App for University Students to Manage Expenses - Jonathan, Sidi; Lau, Sue Nee (IEEE, 2026)
eSaku is an interactive mobile application designed to help university students manage their finances more effectively. The development process follows the Rapid Application Development (RAD) methodology, which emphasizes iterative design and user feedback to create a functional and user-friendly product. Data for the app’s design and features were gathered through surveys conducted among university students to ensure that it meets their specific financial management needs. The aim of eSaku is to provide students with a comprehensive tool that enables them to track their expenses, plan budgets, set financial goals, and monitor their spending habits. The app includes key features such as income and expense tracking, semester-based budgeting, goal setting for savings, and payment reminders for academic-related expenses. Users can categorize financial records and analyze their spending through visual charts, while its intuitive interface allows easy navigation across various financial tasks. By focusing on the essential financial management needs of university students, eSaku aims to help students understand their financial habits, make informed decisions, and achieve their financial goals through a simple and efficient mobile platform.